2013
DOI: 10.5539/jfr.v2n2p55
|View full text |Cite
|
Sign up to set email alerts
|

Proteolytic Activity in Actomyosinfrom Mantle and Fin of Squid (Illexargentinus) Stored at 2-4°C. Influence on the Physicochemical and Functional Properties of the Protein

Abstract: Actomyosin (AM) of mantle and fin from squid was stored at 2-4°C and the possible presence of proteolytic activity was investigated. Similar SDS-PAGE 10% patterns were obtained with both AM at zero time of storage. In absence of protease inhibitors, a decrease in the intensity of the band of the myosin heavy chain (MHC) and an increase in those of 155 kDa and 55 kDa bands of stored AM was observed. In presence of either PMSF (phenylmethylsulfonyl fluoride) or EDTA (ethylenediaminetetraacetic acid) both AM show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 31 publications
1
9
0
Order By: Relevance
“…Figure 2 shows that the EAI values for the emulsions formulated with squid mantle MF were significantly (p<0.05) higher (34.2%) than those formulated with weakfish MF. The higher EAI values obtained for the mantle, as compared to those obtained for weakfish, could be related to the proteolytic activity present in the properties (MIGNINO et al, 2008(MIGNINO et al, , 2013. The EAI of the mixture showed intermediate values between those from squid and weakfish.…”
Section: Functional Properties Of the Squid Mantle And Weakfishmentioning
confidence: 72%
See 1 more Smart Citation
“…Figure 2 shows that the EAI values for the emulsions formulated with squid mantle MF were significantly (p<0.05) higher (34.2%) than those formulated with weakfish MF. The higher EAI values obtained for the mantle, as compared to those obtained for weakfish, could be related to the proteolytic activity present in the properties (MIGNINO et al, 2008(MIGNINO et al, , 2013. The EAI of the mixture showed intermediate values between those from squid and weakfish.…”
Section: Functional Properties Of the Squid Mantle And Weakfishmentioning
confidence: 72%
“…The characteristics of the myofibrillar proteins, the proteins mostly responsible for the functional properties, are of great importance for the elaboration of gel products (XIONG, 1997). Some cephalopod species show poor gelling capacity due to high proteolytic activity, affecting one of the major myofibrillar proteins (HURTADO et al, 1999;GÓMEZ-GUILLÉN et al, 2002, and studies with Illex argentines have revealed the presence of proteolytic activity during frozen storage MIGNINO et al, 2008MIGNINO et al, , 2013. Studies on cephalopods have reported a decrease in gel strength due to the presence of proteolytic activity that degrades the heavy myosin chain (NAGASHIMA et al, 1992;GÓMEZ-GUILLÉN et al, 2002.…”
Section: Biochemical and Functional Properties Of The Gel Pastes Frommentioning
confidence: 99%
“…The peak of proteolytic activity around 40 o C has been attributed to the specific activity of neutral serine proteases in other cephalopod species (Ebina et al, 1995;Ayensa et al, 1999). Both serin and metallo proteases were recently reported in stored isolated squid actomyosin (Mignino et al, 2013). The presence of proteolytic activity would not allow the manifestation of the setting capacity in the mantle paste.…”
Section: Discussionmentioning
confidence: 99%
“…Assays in which this paste was formulated, with the addition of 2mM of ethylendiaminetetracetic acid (EDTA) or 1mM of meat phenylmethylsulfonyl fluoride (PMSF), were also made. EDTA has been described as an inhibitor of metal proteinases due to chelating power (Mignino, Crupkin, & Paredi, 2013). PMSF is a characteristic inhibitor of serin-proteases (Mignino et al, 2013).…”
Section: Preparation Of Gelsmentioning
confidence: 99%
See 1 more Smart Citation